Quasi‐interpolation by splines on the uniform knot sets - Leetma, Evely; Vainikko, Gennadi (Mathematical Modelling and Analysis, 2007)
In the case of uniform grids, the error of the spline interpolant of a function defined on R has been well estimated. On the basis of the spline interpolation formula for functions defined on R we derive quasi‐interpolation formulae for functions defined on R or in a vicinity of a bounded interval, say [0,1], and we estimate the difference between the interpolant and the quasi‐interpolants.First Published Online: 14 Oct 2010